"Bath salt" use among a nationally representative sample of high school seniors in the United States. (14th July 2015) - Palamar, Joseph J.
<x xml:space="preserve">Abstract</x> Background and Objectives "Bath salts" are new drugs which have received extensive media attention. However, national studies in the US have not investigated prevalence or correlates of use. Methods Data were examined from Monitoring the Future, a representative sample of US high school seniors (2012–2013, N = 8, 604). Results Only 1.1% of high school seniors used "bath salts" in the last year and the strongest correlate of use was use of other drugs. Discussion and Conclusions "Bath salt" use is not very prevalent, but users of other drugs are at highest risk for use. Scientific Significance We must continue to monitor new drugs in order to inform prevention and quickly detect potential epidemics. (Am J Addict 2015;24:488–491)